Antioxidant Activity Of Body Lotion Formula Containing Rosella Petal Extract (Hibiscus sabdariffa) And Calamansi Orange Peel Essential Oil (Citrofortunella microcarpa) - Suci Rahmawati; Oky Hermansyah; Rose Intan Perma Sari; Yendha Dwi Rolitta; Dwi Kurnia Putri; Tri Danang Kurniawan (Jurnal Pharmacopoeia, 2026)
Rosella petals contain anthocyanins, and calamansi orange peel essential oil contains limonene, both of which are antioxidant compounds. Antioxidants capture free radicals, allowing them to serve as active ingredients in preventing premature aging in skincare products such as body lotions. This study was aimed to formulate and test of the antioxidant level from body lotion formula containing roselle petal extract (Hibiscus sabdariffa L.) and calamansi orange peel essential oil (Citrofortunella microcarpa). Roselle petal extract was extracted by maceration method using 96% ethanol and calamansi essential oil was obtained by distillation using aquades. Body lotion formula was designed in three formulas (F1, F2, and F3) with differing concentrations of roselle extract and calamansi essential oil, respectively: F1 (1% and 3%), F2 (2% and 5%), and F3 (4% and 7%). The formulations were evaluated their physical properties (organoleptic characteristics, homogeneity, pH, spread ability, viscosity, and stability) and also antioxidant activity. The evaluation results were indicated that all formulations met physical standards but were unstable under heat. F1, F2, and F3 were semi-solid, homogeneous, pink in color, and had a distinctive calamansi aroma. The antioxidant evaluation yielded IC₅₀ values of 89.9 ppm, 81.7 ppm, and 69.7 ppm for F1, F2, and F3, respectively. In this study can be concluded that F3 formula had the highest antioxidant activity. This study was demonstrated that increasing the concentration both of roselle petal extract and essential oil of calamansi enhanced the antioxidant degree of body lotion formula.